2014
DOI: 10.1021/am505416m
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polymer Energy Level Shifts in Lithium-Ion Battery Electrolytes

Abstract: The ionization potentials (IPs) and electron affinities (EAs) of widely used conjugated polymers are evaluated by cyclic voltammetry (CV) in conventional electrochemical and lithium-ion battery media, and also by ultraviolet photoelectron spectroscopy (UPS) in vacuo. By comparing the data obtained in the different systems, it is found that the IPs of the conjugated polymer films determined by conventional CV (IPC) can be correlated with UPS-measured HOMO energy levels (EH,UPS) by the relationship EH,UPS = (1.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…In the solid state, the absorption onset for polymer p(gNDI-gT2) is at 1,550 nm ( Supplementary Fig. 1 ) and for p(gNDI-T2) at 817 nm which is consistent with an increased donor strength of the glycol-bithiophene unit compared to bithiophene unit and in agreement with literature 22 23 . The initial UV-Vis spectrum of p(gNDI-gT2) has two absorption peaks, a π - π * transition located between 350 and 550 nm and a broad absorption band from an intramolecular charge transfer complex (ICT) between 600 and 1,550 nm.…”
Section: Resultssupporting
confidence: 89%
“…In the solid state, the absorption onset for polymer p(gNDI-gT2) is at 1,550 nm ( Supplementary Fig. 1 ) and for p(gNDI-T2) at 817 nm which is consistent with an increased donor strength of the glycol-bithiophene unit compared to bithiophene unit and in agreement with literature 22 23 . The initial UV-Vis spectrum of p(gNDI-gT2) has two absorption peaks, a π - π * transition located between 350 and 550 nm and a broad absorption band from an intramolecular charge transfer complex (ICT) between 600 and 1,550 nm.…”
Section: Resultssupporting
confidence: 89%
“…Conducting polymers, such as conjugated polymers, have been the subject of recent interest due to the high conductivity and the designability of the electronic property, making them broad applications as conductive binders, surface functional materials and electrode materials in rechargeable batteries . Recent studies revealed that promising energy storage performance can be achieved for conducting polymers as LIB electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this structural alteration causes an increase in the IE of p(g 4 2T‐T) as compared to P3HT. Similar polymers with various oligo ethylene glycol side chains were recently used as the anode material in lithium‐ion batteries and as the active layer in electrochemical transistors . Polar side chains enable the use of more polar solvents such as acetonitrile and dimethylformamide (DMF), which offer better solubility for polar molecular dopants such as F4TCNQ.…”
mentioning
confidence: 99%
“…The g 4 2T‐T monomer was synthesized according to a modified procedure reported by Song et al (see Figure and the Supporting Information for experimental details). Stille polycondensation yielded p(g 4 2T‐T) with a number‐average molecular weight M n ≈ 16 kg mol −1 (Figure S1, Supporting Information) and an optical bandgap of 1.68 eV (Figure S2, Supporting Information).…”
mentioning
confidence: 99%